"Double Hit" Homozygous Mutations for Two Different Rare Inborn Errors of Metabolism: A Burden for Countries with High Prevalences of Consangineous Marriages - Asburçe Olgaç; Leyla Tümer; Serdar Ceylaner; Gürsel Biberoğlu; Alev Hasanoğlu (Galenos Yayinevi, 2018)
Inborn errors of metabolism comprise a broad range of genetic diseases of which most are inherited in an autosomal recessive manner. Although being rare, there is a significant increase in their rate especially in countries where consanguineous marriages are performed. Isovaleric aciduria is an organic aciduria characterized by abnormal leucine metabolism resulting from a deficiency in the enzyme isovaleryl-CoA dehydrogenase. Niemann-Pick disease Type C is a rare autosomal recessive inherited disorder involving the intracellular transport of endocytosed cholesterol with sequestration of unesterified cholesterol in lysosomes and late endosomes. Both of these disorders are rarely encountered inborn errors of metabolism. We report a case of a boy with marked jaundice and hepatosplenomegaly, who was later diagnosed as isovaleric aciduria and Niemann-Pick disease Type C concomitantly. The diagnoses were proven by genetic analyses. A novel mutation for Niemann-Pick Type C has also been defined in this case report.